2016
DOI: 10.1002/ana.24701
|View full text |Cite
|
Sign up to set email alerts
|

Reply

Abstract: We thank Lien and colleagues for their letter in response to our recent publication 1 describing a patient with epileptic encephalopathy harboring a novel de novo GABRB1 mutation, T287I. The phenotypes of this patient are similar to those of the patient with the epileptic encephalopathy infantile spasms, and the GABRB1 (F246S) mutation, that was reported by the Epi4K consortium in 2013. 2 In this article, the GABRB1 mutation was found in only the 1 patient, and GABRB1 had not been previously associated with ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…Moreover, changes in the physiological and biochemical properties of β3-containing GABA A R assemblies in the brains of patients with epilepsy (Menzikov et al, 2021). Several studies have reported that GABRB3 mutations with juvenile myoclonic epilepsy, childhood absence epilepsy, and/or other syndromes and that reduced GABA A R function causes an E: I imbalance (Gurba et al, 2012;Janve et al, 2016). Animal models of epilepsy have demonstrated obvious alterations in the expression and rearrangement of GABA A R subunits in the hippocampus and the parahippocampal areas, including downregulation of the α5 and δ subunits and upregulation of the α4 subunit (Sperk et al, 2021).…”
Section: Epileptic Seizuresmentioning
confidence: 99%
“…Moreover, changes in the physiological and biochemical properties of β3-containing GABA A R assemblies in the brains of patients with epilepsy (Menzikov et al, 2021). Several studies have reported that GABRB3 mutations with juvenile myoclonic epilepsy, childhood absence epilepsy, and/or other syndromes and that reduced GABA A R function causes an E: I imbalance (Gurba et al, 2012;Janve et al, 2016). Animal models of epilepsy have demonstrated obvious alterations in the expression and rearrangement of GABA A R subunits in the hippocampus and the parahippocampal areas, including downregulation of the α5 and δ subunits and upregulation of the α4 subunit (Sperk et al, 2021).…”
Section: Epileptic Seizuresmentioning
confidence: 99%